ASPEK-ASPEK KEPEMIMPINAN MASYARAKAT DALAM MENDORONG PEMBANGUNAN DI ERA REFORMASI DAN OTONOMI DAERAH - man, Herman man (Makassar Journal of Social Sciences, 2013)
The dynamics of community life in the era of reform and autonomy of blood very quickly. Along with it, the construction of a keyword to Membincang the community life better, prosperous, independent and religious. The collar condition seems not easy and fast to be realized. Therefore very many factors that must be involved and require attention especially to the leaders as the locomotive development process. Leadership one of which determine the success of the development process. Aspects of leadership in the community also become urgent to assess its contribution in the development process. The latter was, in every region is no exception in South Sulawesi local wisdom in the community still has historically maintained in the socio-cultural aspects of concrete existence in the mind, heart and attitude behavior. Numun existence in providing leadership role and influence in a leader sometimes left behind and more neglected. Whereas integrated both the spirit as well as the spirit of absolute power-existence in a leader.